2022
DOI: 10.3171/2021.10.focus21496
|View full text |Cite
|
Sign up to set email alerts
|

Learning curves in robot-assisted spine surgery: a systematic review and proposal of application to residency curricula

Abstract: OBJECTIVE Spine robots have seen increased utilization over the past half decade with the introduction of multiple new systems. Market research expects this expansion to continue over the next half decade at an annual rate of 20%. However, because of the novelty of these devices, there is limited literature on their learning curves and how they should be integrated into residency curricula. With the present review, the authors aimed to address these two points. METHODS A systematic review of the published En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Subanalyses were performed for surgical indications, and the number of levels operated on that had more than the recommended learning period of 20 cases. 13 These included spondylolisthesis, pseudarthrosis/hardware failure, 2-level, 3-level, and 4-or-more-level cases. A linear relationship was observed between case number and operative time when evaluating patients with spondylolisthesis (−0.63 minutes/case, r = 0.41, P < .001), 2-level involvement (−0.35 minutes/case, r = 0.19, P = .05), and 4-or-more-level involvement (−1.29 minutes/case, r = 0.24, P = .05).…”
Section: Resultsmentioning
confidence: 99%
“…Subanalyses were performed for surgical indications, and the number of levels operated on that had more than the recommended learning period of 20 cases. 13 These included spondylolisthesis, pseudarthrosis/hardware failure, 2-level, 3-level, and 4-or-more-level cases. A linear relationship was observed between case number and operative time when evaluating patients with spondylolisthesis (−0.63 minutes/case, r = 0.41, P < .001), 2-level involvement (−0.35 minutes/case, r = 0.19, P = .05), and 4-or-more-level involvement (−1.29 minutes/case, r = 0.24, P = .05).…”
Section: Resultsmentioning
confidence: 99%
“…19 By contrast, the entry point and trajectory were automatically identified in RA methods, which required short learning curves for surgeons. 32 Moreover, the arm of the robotic system can operate in a real-time dynamic compensation mode, thereby reducing error-prone movements and improving insertion accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Urakov et al showed no significant difference in the speed of pedicle screw instrumentation based on the years of experience or dedication to spine surgery (39). A recent systematic review demonstrated a threshold of 20-30 cases and proposed an application of robotic spine surgery to residency curricula (40).…”
Section: Commentsmentioning
confidence: 99%
“…Urakov et al showed no significant difference in the speed of pedicle screw instrumentation based on the years of experience or dedication to spine surgery ( 39 ). A recent systematic review demonstrated a threshold of 20–30 cases and proposed an application of robotic spine surgery to residency curricula ( 40 ). In our training program, fellows rotate through MISS blocks for 3 months where they are exposed to robotic spine surgery, spinal navigation technology, and percutaneous pedicle screw placement using fluoroscopic- and navigation-guidance.…”
Section: Commentsmentioning
confidence: 99%